INTEGRASI APLIKASI WEB DAN SMS GATEWAY PADA TPI GEMPOLSARI MENGGUNAKAN PHP DAN MySQL - Adiyanto, Adiyanto; Suraya, Suraya; Sutanta, Edhy (Jurnal Jarkom, 2013)
ABSTRACT Â Fish Auction ( TPI ) Gempolsewu Village in Kendal as a place to conduct the auction of fish the fishermen who sell fish to consumers by intermediaries TPI . TPI is managed by KUD " Mina Jaya " and in the supervision of the Department of Marine Government Kendal . Constraints faced by TPI is usually caused because the board came late while the tender process has been conducted , resulting in personnel handling the tender process is reduced and inhibit the auction process and the data collection process of buying and selling is done manually so it takes a long time , pricing information can not be known society at large , and frequent data recording errors . This study builds web applications and sms integration gateway for sending information to many consumers and simultaneously TPI board . Applications built using the PHP programming language , MySQL database , and for Gammu SMS Gateway application , as well as Macromedia Dreamweaver 8 , Adobe Photoshop CS3 , and supporting software Xampp 1.6.8 . With this application the consumer does not have to come directly to TPI to know the latest price of fish and as a medium for ordering fish online services . Applications built features for data processing officers, members , fish , boat , and fish purchases and auctions . Applications are built to be developed to make the SMS auto-reply , displays the name of the sender and recipient of the SMS that has been stored in the phonebook , and SMS distinguish already and unread .